Massive Facial Presentation of Dermatofibrosarcoma Protuberans - Sebastiaan Hermans; Karlijn Clarysse; David Emmanuel Las; Johan de Mey; Maurice Yves Mommaerts; Yannick De Brucker (Case Reports in Radiology)
Dermatofibrosarcoma protuberans is a low-grade cutaneous sarcoma typically located on the trunk or proximal extremities. Less common locations include the head, face, and neck area. This tumour is slow growing with variable clinical appearance. It is known for its locally invasive nature and low metastatic propensity. Because imaging findings are rather nonspecific, biopsy is needed for definite diagnosis. This case describes an unusually large example of dermatofibrosarcoma protuberans in the less common preauricular region.